2017
DOI: 10.1111/cen3.12416
|View full text |Cite
|
Sign up to set email alerts
|

Expression of CCL5 is induced by polyinosinic : polycytidylic acid in cultured hCMEC/D3 human brain microvascular endothelial cells

Abstract: Objective Brain microvascular endothelial cells are one of the cell types that form the blood-brain barrier, and play an important role in the defense system of the brain. Toll-like receptor 3 (TLR3) is a pattern-recognition receptor against double-stranded RNA, and TLR3 signaling is important in antiviral innate immune reactions. However, TLR3 signaling in brain microvascular endothelial cells is not well understood. We aimed to investigate the role of TLR3 signaling in chemokine CCL5 production in human brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…19 We have previously reported that the treatment of hCMEC/D3 cells with poly IC induces the expression of CCL5 in an IFN-b-independent manner, 15 whereas CXCL10 20 and ISG60 17 are induced by poly IC in an IFN-b-dependent manner. 19 We have previously reported that the treatment of hCMEC/D3 cells with poly IC induces the expression of CCL5 in an IFN-b-independent manner, 15 whereas CXCL10 20 and ISG60 17 are induced by poly IC in an IFN-b-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…19 We have previously reported that the treatment of hCMEC/D3 cells with poly IC induces the expression of CCL5 in an IFN-b-independent manner, 15 whereas CXCL10 20 and ISG60 17 are induced by poly IC in an IFN-b-dependent manner. 19 We have previously reported that the treatment of hCMEC/D3 cells with poly IC induces the expression of CCL5 in an IFN-b-independent manner, 15 whereas CXCL10 20 and ISG60 17 are induced by poly IC in an IFN-b-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, the cells were transfected with siRNA and were incubated for 48 h. The transfected cells were treated with poly IC for the indicated period and Figure 2 RNA interference against Toll-like receptor (TLR3) results in the decrease in polyinosinic-polycytidylic acid (poly IC)-induced expression of C-C motif chemokine ligand 2 (CCL2). 15 Data are shown as the mean AE SD (n = 3; *P < 0.05, **P < 0.01 by t-test). After 48 h treatment, the cells were treated with 30 lg/mL poly IC.…”
Section: Cell Culture Rna Interference and Inhibitorsmentioning
confidence: 99%
See 3 more Smart Citations